Analisa Parkir On Street Progresif pada Penerapan QRIS Di Jalan Jendral Ahmad Yani Jember: Analysis of Progressive On Street Parking on the Implementation of QRIS on Jalan Jendral Ahmad Yani, Jember - Sudahnan, Mytha Dwi; Hamduwibawa, Rofi; Abadi, Taufan; Amijaya, Jimi (Jurnal Rekayasa Infrastruktur HEXAGON, 2024)
The economic growth in Madiun City make shows good development has made Guest House entrepreneurs start to experience an increase. One of them is the construction of Guest House A. To find out that the investment is considered feasible, it is necessary to carry out a feasibility study analysis from an economic perspective by considering several indicators, including the Net Present Value, Net Benefit Cost Ratio, Internal Rate of Return, and Back Period. From the calculations that have carried out, the NPV value is 1,053,103,006.39, the Internal Rate of Return is 12,60%, the Benefit of Cost is 2.13, with a Payback Period of 10.93 Years. From the existing analysis, the NPV is more than zero for IRR value is greater than the MRR value, and the B/C value is greated than one, with existing indicators concluding that the investment can be continue